Cardiac remodeling on echocardiogram is related to contrast-associated acute kidney injury after coronary angiography: a cross-section study - Chen, Qingqing; Li, Duanbin; Jiang, Hangpan; Hu, Tianli; Tao, Yecheng; Du, Changqing; Zhang, Wenbin (Frontiers in Cardiovascular Medicine, 2023)
Background Cardiac dysfunction is a well-established risk factor for contrast-associated acute kidney injury (CA-AKI). Nevertheless, the relationship between cardiac remodeling, as assessed by echocardiography, and CA-AKI remains uncertain. Method A total of 3,241 patients undergoing coronary angiography (CAG) with/without percutaneous coronary intervention (PCI) were enrolled in this retrospective study. Collected echocardiographic parameters were normalized by body surface area (BSA) and divided according to quartile, including the left ventricular internal end-diastolic diameter index (LVIDDI), left ventricular internal end-systolic diameter index (LVIDSI), and left ventricular mass index (LVMI). Logistic regression analysis was conducted to ascertain the association between structural parameter changes and CA-AKI. Further investigation was performed in different subgroups. Results The mean age of the participants was 66.6 years, and 16.3% suffered from CA-AKI. LVIDSI [≥22.9 mm/m2: OR = 1.953, 95%CI (1.459 to 2.615), P < 0.001], LVIDDI [≥33.2 mm/m2: OR = 1.443, 95%CI (1.087 to 1.914), P = 0.011], and LVMI [≥141.0 g/m2: OR = 1.530, 95%CI (1.146 to 2.044), P = 0.004] in quartile were positively associated with CA-AKI risk in general (all P for trend <0.05). These associations were consistent when stratified by age, left ventricular ejection fraction, estimated glomerular filtration rate, and N-terminal brain natriuretic peptide (all P for interaction >0.05). The presence of eccentric hypertrophy [OR = 1.400, 95%CI (1.093 to 1.793), P = 0.008] and the coexistence of hypertrophy and dilation [OR = 1.397, 95%CI (1.091 to 1.789), P = 0.008] carried a higher CA-AKI risk. Conclusion The presence of cardiac remodeling, assessed by echocardiography, is associated with a higher risk of CA-AKI.